The Effect of Hybrid Learning on Students' Psychological Well-Being during the Post-Pandemic Transition - Darmawan, Adichandra Febryana Yuscatama (Worldwide Research Publishing, 2025)
The post-pandemic transition brought significant changes in the higher education system, with hybrid learning becoming the dominant model. However, its impact on the psychological well-being of students has not been comprehensively explored. This study aims to analyze the influence of the intensity and configuration of hybrid learning on the dimensions of students' psychological well-being, as well as identify moderator factors such as digital literacy and belonging. The study uses a quantitative approach with an explanatory survey design. A sample of 250 students was selected through proportional stratified random sampling. The research instruments were questionnaires based on Ryff's Psychological Well-Being Scales (RPWB) and the hybrid learning intensity scale. Data were analyzed using multiple linear regression, Pearson correlation, and thematic analysis from semi-structured interviews. The results showed that offline presence had a significant effect on the dimensions of positive relations and self-acceptance, while asynchronous involvement contributed to autonomy and personal growth. Online synchronous sessions strengthen purpose in life and academic engagement. Digital literacy has been proven to increase environmental mastery, while a sense of belonging strengthens purpose in life and positive relationships. These findings confirm that a balanced hybrid learning design, supported by digital literacy and community building strategies, plays an important role in improving students' psychological well-being in the post-pandemic transition period.